1997
DOI: 10.1111/1468-0084.00061
|View full text |Cite
|
Sign up to set email alerts
|

Regional Migration in Spain: The Effect of Personal Characteristics and of Unemployment, Wage and House Price Differentials Using Pooled Cross‐Sections

Abstract: "The purpose of this paper is to identify which regional economic factors influence male migration decisions [in Spain], taking into account personal characteristics....[We present] evidence on the importance...of the person's situation, in particular: (i) family characteristics, such as being married to a working woman, having children, or living with relatives (ii) personal factors such as education or age, and (iii) own employment situation such as being registered as unemployed as opposed to non-registered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
148
0
10

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(172 citation statements)
references
References 13 publications
14
148
0
10
Order By: Relevance
“…Jimeno and Bentolila (1998) point out that migration decisions are poorly sensitive to the unemployment rate and real wages. Antolin and Bover (1997) conclude that the unemployment rate has no significant effect on international migration and show that emigration occurs from regions where wages are higher than the average, which seems to contradict many of the theoretical findings. These conflicting conclusions are not only observed for the case of Spain, since Italian internal migrations do not react to mass unemployment, as Fachin (2007) found, nor to an increase in GDP, as determined by Biagi and Faggian (2011).…”
Section: Introductionmentioning
confidence: 59%
“…Jimeno and Bentolila (1998) point out that migration decisions are poorly sensitive to the unemployment rate and real wages. Antolin and Bover (1997) conclude that the unemployment rate has no significant effect on international migration and show that emigration occurs from regions where wages are higher than the average, which seems to contradict many of the theoretical findings. These conflicting conclusions are not only observed for the case of Spain, since Italian internal migrations do not react to mass unemployment, as Fachin (2007) found, nor to an increase in GDP, as determined by Biagi and Faggian (2011).…”
Section: Introductionmentioning
confidence: 59%
“…For Great Britain (Jackman and Savouri 1992; Pissarides and Wadsworth 1989;Hughes and McCormick 1989), Sweden (Westerlund 1998;Harkman 1989), and the Netherlands (Van Djik et al 1989), there is nearly invariable empirical evidence in favour of higher migration rates among the unemployed. However, for Spain (Antolin and Bover 1997) and Finland (Tervo 2000), there are no reports of more frequent migration among the unemployed. These inconsistent results reflect methodological issues (Sandefur and Tuma 1987;Greenwood 1997: 651 et seq.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Jimeno and Bentolila have shown that "the responses of migration and participation to rates to labor demand shocks, seem to be significantly slower than in the US states and EU regions" (1998, p. 46). Antolin and Bover (1997) report that "migration does not seem to be working as a mechanism for alleviating the very high levels of unemployment in Spain" (1997, p. 230). They attribute this in part to an individuals' family situation and in part to the unemployment registration system which appears to have a direct negative effect on the probability of migration.…”
Section: What Can Be Done To Reduce Unemployment In Eastern and Centrmentioning
confidence: 99%